Zoom Fatigue dan Keberfungsian Sosial di Kalangan Mahasiswa - Kuntardi, Dina Vebiola Saraswati (Jurnal Publisitas, 2021)
Since the outbreak of Covid-19, many virtual communication platforms has been increasingly used. One of them is as a substitute for direct learning to students. This activity is known as online learning which is usually done through Zoom, Cisco Webex, Whatsapp Group (WAG), Google Meet, etc. Although the use of this virtual communication platform supports learning, one day its existence actually made students tired. This condition is known as zoom fatigue. Meanwhile, the social functioning of each person should also be taken into account in this pandemic, especially if he experiences zoom fatigue. In connection with this, this research is directed to find out how the social functioning of students after experiencing zoom fatigue. This research was conducted using descriptive qualitative methods. The results showed that students experienced difficulties both in fulfilling their basic needs, carrying out their social roles, and in overcoming their problem